Model Strategi Adaptasi Kelompok Wanita Tani (KWT) Melalui Digital Marketing Sebagai Penanggulangan Pandemi COVID-19 - Yeni Pramita; Keppi Sukesih; Reza Safitri (Jurnal Penyuluhan, 2023)
The Covid-19 pandemic has had an impact on socio-economic changes globally, including at KWT Sri Rejeki. KWT Sri Rejeki has superior local food products that already use a modern touch in their packaging, but sales are still far above the average before the pandemic. This study aims to formulate a model of adaptation strategy of KWT Sri Rejeki through Digital Marketing. The research uses action research to gain knowledge as well as to take action to create change in KWT Sri Rejeki. In-depth interviews and field observations to get a diagnosis of the problem in order to determine an action plan, implementation and evaluation. Data analysis uses In Vivo Coding which is then followed by Pattern Coding by using short words or short phrases obtained through the informant's sentences. The results showed that the adaptation strategy model at KWT Sri Rejeki was conducting marketing analysis, marketing formulation, and marketing implementation and then integrated training was carried out to improve hard skills and soft skills and then developed a plan followed by a presentation. After being presented, it is then implemented in a business unit owned by KWT Sri Rejeki after an evaluation has been carried out as a reflection of the effectiveness of the strategy model that has been formulated.